(untitled) (Journal of Decolonising Disciplines, 2021)
The #RhodesMustFall (RMF) movement of 2015 and 2016 challenged universities across the nation to interrogate how the curriculum serves as an alienating and marginalising device that stymies student success. Consequently, the HE sector has been challenged to respond to student calls for decolonisation by reviewing existing university curricula which promote forms of knowledge production that do not reflect an African worldview or a global South context. Academics have refocused their attention on exploring what an alternative, decolonial curriculum would entail. This paper reports on a professional development course, designed to support academics to ‘decolonise their curricula’, and explores what it meant to facilitate and participate in a course that disrupted who they were as disciplinary experts in the university. Drawing on decolonial scholarship, the authors use auto-ethnography to engage with two disciplines, namely midwifery and journalism, to see how the metaphors of (de)coloniality surfaced in these disciplines and how they were mediated through a decolonial approach to course re-design and re-imagination.